Evaluation of parent-reported feeding practices in a racially diverse, treatment-seeking child overweight/obesity sample. Issue 3 (3rd July 2017) - Lydecker, Janet A.; Simpson, Courtney; Kwitowski, Melissa; Gow, Rachel W.; Stern, Marilyn; Bulik, Cynthia M.; Mazzeo, Suzanne E.
ABSTRACT: This study examined psychometric properties and baseline/post-treatment racial differences in the Child Feeding Questionnaire (CFQ) in parents of overweight/obese children in a randomized controlled obesity trial. Participants were 302 ( n  = 285 mothers, n  = 17 fathers) diverse ( n  = 207 Black, n  = 80 White), treatment-seeking parents of children (5–11 years) with overweight/obesity. CFQ data fit the established Anderson factor structure in the full sample and subsample of Black parents. Black parents had higher scores than White parents on only Pressure to Eat . The CFQ yields reliable and valid scores in a racially diverse treatment-seeking sample, suggesting its utility in culturally-sensitive pediatric obesity treatment.